Synthesis and Characterization of Sodium Aluminate from Aluminum and Sodium Hydroxide - Dinalia Dinalia; Syamsi Aini; Jon Efendi (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
The synthesis of sodium aluminate from aluminum and sodium hydroxide was successfully conducted to optimize its potential as a precursor for zeolite production. Aluminum was reacted with NaOH solution under continuous stirring for five hours, with variations in pH and Al-to-NaOH molar ratio to determine optimal synthesis conditions. The highest aluminum conversion (94.33%) was achieved at pH 13.6 and an Al-to-NaOH molar ratio of 1:4. Fourier-transform infrared (FTIR) spectroscopy confirmed the formation of tetrahedral [AlO₄]⁻ units through characteristic aluminate vibrational bands at 624 and 727 cm⁻¹. X-ray diffraction (XRD) analysis revealed sharp reflections at 2θ ≈ 34.8°, corresponding to crystalline NaAlO₂ (JCPDS No. 33-1200), indicating high crystallinity and phase purity. Scanning electron microscopy coupled with energy-dispersive X-ray (SEM–EDX) analysis showed irregular plate-like crystalline particles with a near-stoichiometric Na:Al ratio ( 1:1), confirming compositional homogeneity. Overall, optimized alkalinity and stoichiometry were found to be critical for producing highly crystalline and compositionally pure sodium aluminate, suggesting its suitability as a high-quality, environmentally friendly precursor for zeolite synthesis.